NEW PYRIDINE-3-SULFONATO TIN (IV), ANTIMONY (III) AND (V) HALO ADDUCTS AND COMPLEXES: SYNTHESIS AND INFRARED STUDY - AÏSSATOU GUEYE; MOUHAMADOU BIRAME DIOP; LIBASSE DIOP (Journal of Engineering Studies and Research)
Six new tin (IV), antimony (III) and antimony (V) adducts and complexes have been synthesized. Discrete structures were suggested on the basis of infrared data. Within the structures, the anion behaves as a bidentate, monochelating and monodentate, monodentate and tri O-chelating ligand. The environments around metallic centres are octahedral. Considering preamble of extra hydrogen bonds in compounds containing water molecules and/or OH groups, supramolecular architectures may be given rise.